Diversidade de Briófitas na Reserva Ducke, Manaus, Amazonas. Musgos (Bryophyta) - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2007)
The Adolpho Ducke Forest Reserve is a preserved stretch of primary terra firme forest in the Amazon. Currently it has been suffering with the deforestation process due to its proximity to the city of Manaus. As it is located in the center of the Amazon, it probably has a very diverse brioflora that has not yet been properly studied. This work aims to expand the knowledge base of the Brazilian brioflora, specifically of mosses (Bryophyta) and to compare it qualitatively with the data already obtained in the Caxiuanã National Forest in the state of Pará. The results of this project were obtained through the analyses of samples collected by a team from MPEG in the PPBIO - Rserva Ducke plot area in January 2006. The samples were examined by preparing slides with magnifying glasses and identified by light microscopy and specialized bibliography. The bibliographical survey indicated the occurrence of 9 families and 30 species, among which 7 families and 11 species are found in the Ducke Reserve, while the study of the samples indicated the occurrence of 8 families and 18 species. The families and species that most occurred were: Fissidens pellucidus Hornsch. varo pellucidus, Octoblepharum pulvinatum Dozy & Molk, Leucobryum martinum (Hornsch.) Müll.Hall and Sematophylum subsimplex (Hedw.) Mitt. The most used substrate is corky (occurs on live tree trunks), with 27 occurrences for Octoblepharum pulvinatum, 16 for Leucobryum martianum and 14 for Sematophylum subsimplex. It should be emphasized that the research is still in progress, so the results are not conclusive and these numbers may change as more samples are studied. A great variety of species and families can be observed at the Ferreira Penna Scientific Station and at the Ducke Reserve.
Diversity of Bryophytes in the Reserva Ducke, Manaus, Amazonas. Mosses (Bryophyta)
Keywords: Briófitas; Diversidade; Musgos; Taxonomia; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL